Acalculous Acute Cholecystitis in Previously Healthy Children: General Overview and Analysis of Pediatric Infectious Cases. (11th November 2015) - Poddighe, Dimitri; Tresoldi, Matteo; Licari, Amelia; Marseglia, Gian Luigi
Abstract : Acute acalculous cholecystitis (AAC) is an inflammation of the gallbladder, which does not appear to be associated with the presence of gallstones. AAC is estimated to represent more than 50% of cases of acute cholecystitis in the pediatric population. Although this pathology was initially described in critically ill patients, actually most pediatric cases have been observed during several infectious diseases. Particularly, here we reviewed pediatric infectious acute acalculous cholecystitis and analyzed the pathophysiological and clinical aspects of bacterial and viral forms.